Wind resource assessment offshore the Atlantic Iberian coast with the WRF model. (15th February 2018) - Salvação, N.; Guedes Soares, C.
Abstract: A ten year wind hindcast is presented for the Iberian Peninsula coast. Simulations are conducted with the WRF model at 9 and 3 km of spatial resolution and 6 hourly output. The amount of energy that can be generated by an energy conversion device as well as the annual operating hours and capacity factors are estimated and presented as wind resource maps. The spatial variation of the error and the annual and seasonal variations of the wind energy resource are also depicted. Comparisons with observational data show the WRF model is a proficient wind generating tool, whether in coastal waters as in the open ocean, even when the model is run at a lower spatial resolution. The results show that wind farm planning offshore the Iberian coast is an eligible choice, with average annual energy density reaching up to 971 W/m 2, 549 W/m 2 and 398 W/m 2 in the north, centre and southern regions respectively. The potential production by offshore energy conversion devices in selected sub-regions further indicates that wind farm implementation offshore the Iberian coast will produce high amounts of electricity. Highlights: The wind potential of the Iberian coast is estimated for a 10 year period. Spatial distribution of wind speed and direction error is examined. WRF performance is evaluated for distinct wind speed intervals. Spatio-temporal variability of the offshore wind resources is determined. A wind resource map is presented for the recent decade.